Evaluation of six commonly used reference genes for gene expression studies in herbicide‐resistant Avena fatua biotypes. (25th April 2016) - Wrzesińska, B; Kierzek, R; Obrępalska‐Stęplowska, A
Summary: Avena fatua of the family Poaceae is one of the most common and economically damaging grass weeds. Resistance to herbicides that inhibit acetyl‐coenzyme A carboxylase and acetolactate synthase activities has recently been detected in A. fatua . The resistance may be due to mutations in the herbicide targets and/or enhanced herbicide metabolism resulting from changes in gene expression, including in genes involved in detoxifying herbicide active ingredients. To analyse gene expression, stable housekeeping genes must be experimentally determined and used for data normalisation. In this study, A. fatua plants were treated with different herbicide types and plant materials were harvested at three time points following treatment. Six candidate reference genes (18S rRNA, ACT, EF1α, GAPDH, TBP, and TUB ) were selected, sequenced and analysed by RT‐qPCR. The resulting data were assessed using four algorithms from the RefFinder software to determine gene expression stability. We identified TBP and GAPDH as the most stably expressed A. fatua reference genes following herbicide treatment.